Contrasting trends in heart failure incidence in younger and older New Zealanders, 2006–2018. Issue 4 (22nd October 2021) - Chan, Daniel Z L; Kerr, Andrew; Grey, Corina; Selak, Vanessa; Lee, Mildred Ai Wei; Lund, Mayanna; Poppe, Katrina; Doughty, Rob N
Abstract : Objective: Studies indicate that age-standardised heart failure (HF) incidence has been decreasing internationally; however, contrasting trends in different age groups have been reported, with rates increasing in younger people and decreasing in the elderly. We aimed to describe age-specific trends in HF incidence in New Zealand (NZ). Methods: In this nationwide data linkage study, we used routinely collected hospitalisation data to identify incident HF hospitalisations in NZ residents aged ≥20 years between 2006 and 2018. Age-specific and age-standardised incidence rates were calculated for each calendar year. Joinpoint regression was used to compare incidence trends. Results: 116 113 incident HF hospitalisations were identified over the 13-year study period. Between 2006 and 2013, age-standardised incidence decreased from 403 to 323 per 100 000 (annual percentage change (APC) −2.6%, 95% CI −3.6 to −1.6%). This reduction then plateaued between 2013 and 2018 (APC 0.8%, 95% CI −0.8 to 2.5%). Between 2006 and 2018, rates in individuals aged 20–49 years old increased by 1.5% per year (95% CI 0.3 to 2.7%) and decreased in those aged ≥80 years old by 1.2% per year (95% CI −1.7 to −0.7%). Rates in individuals aged 50–79 years old initially declined from 2006 to 2013, and then remained stable or increased from 2013 to 2018. The proportion of HF hospitalisations associated with ischaemic heart disease decreased from 35.1% in 2006 to 28.0% in 2018. Conclusion: HF remains an important problem in NZ. The decline in overall incidence has plateaued since 2013 due to increasing rates of HF in younger age groups despite an ongoing decline in the elderly.